Gandhi after Gandhi : the relevance of the Mahatma's legacy in today's world - Casolari, Marzia (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Writing about Gandhi without being obvious is always difficult. Numerous books and articles are published every year, especially across the anniversaries of his birth and death. The judicious scholar believes that writing something new on this iconic figure is almost impossible. However, in the difficult times when this book was conceived, at the peak of what presumably can be considered as the worst humanitarian disaster of the 21st century, the Gandhian legacy has become more topical than ever. Gandhi's thought and experience regarding laws and economy, his views on secularism or on the tremendous effects of the colonial rule in India and beyond provide the opportunity to reflect on persistently manipulated constitutions and violated human rights, on the crisis of secularism and the demand of a sustainable, environment friendly economy. This book aims not only to offer new insights into Gandhi's experience and legacy, but to prove how Gandhian values are relevant to the present and can provide explanations and solutions for present challenges. Gandhi After Gandhi will appeal to researchers and students alike interested in Indian culture and political thinking and Indian history since independence"--
Gandhi and the culture of constitutionalism / Pratyush Kumar -- Gandhi and pan-Africanism (1919-1945) / Chiara Corazza -- Gandhi's legacy in South Africa through literature and arts / Carmen Concilio -- "Stride Toward Freedom" : Martin Luther King, the Montgomery Bus Boycott and the Gandhian lesson / Andrea Carosso -- The Mahatma and the Muslims. Gandhi's role in making India's partition inevitable / Michelguglielmo Torri -- Partitions and beyond : Gandhi's views on Palestine's and India's divides / Marzia Casolari -- Rethinking Gandhi's secularism : how did Gandhi's Brahmacarya relate to his last political vision? / Eijiro Hazama -- Gandhi's visionary critique of industrialisation and western civilisation in the light of India's globalized economy / Jagyoseni Mandal -- A nayi, nai talim : reinventing Gandhian education for a new social order. A case study / Pallavi Varma Patil and Roshni Ravi.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Influence; Gandhi, -- Mahatma, -- 1869-1948 -- Political and social views; Nonviolence; India -- Politics and government -- 20th century; HISTORY / General; HISTORY / Asia / India & South Asia; HISTORY / Modern / 20th Century